Exploring the concept of pride from the perspective of Muslim women - Tahir Jan, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
In todayâ€™s fast developing and modern world, Muslim women are faced with so many challenges, especially, when it comes to their attire, faith, and pride. The Hijab, in particular, has become quite a controversial topic in recent years, putting Muslim women in the spotlight about their choices of clothing. This paper discusses those factors, extracted from the review of extant literature, which tend to constitute and form the pride of a Muslim woman in todayâ€™s time and age. It also highlights the role these factors play in enhancing oneâ€™s self-worth. In-depth review of the literature revealed that good and respectable job, sound education, the performance of Hajj or Umrah, and Hijab (covering of head and body) are the main sources of pride for them. Furthermore, this study proposed a conceptual model to be considered for future empirical testing. Lastly, conclusion was drawn based on the review. Â Â